Tertiary treatment of a municipal wastewater toward pharmaceuticals removal by chemical and electrochemical advanced oxidation processes - Francisca C. Moreira (2016)
This study focuses on the degradation of pharmaceuticals from a municipal wastewater after secondary treatment by applying various advanced oxidation processes (AOPs) and electrochemical AOPs (EAOPs) like UVC, H2O2/UVC, anodic oxidation (AO), AO with electrogenerated H2O2 (AO-H2O2), AO-H2O2/UVC and photoelectro-Fenton (PEF) using either UVC radiation (PEF-UVC) or UVA radiation (PEF-UVA). The municipal wastewater after secondary treatment was spiked with 5.0 mg L-1 of trimethoprim (TMP) antibiotic. The efficiency of processes to remove TMP followed the order UVC < AO-H2O2 < PEF-UVA << AO approximate to PEF-UVC < AO-H2O2/UVC < PEF-UVA (pH = 2.8) < H2O2/UVC approximate to PEF-UVC (pH = 2.8), using neutral pH, except when identified. While the UVC radiation alone led to a very low TMP removal, the H2O2/UVC process promoted a very high TMP degradation due to the production of hydroxyl radicals ((OH)-O-center dot) by H2O2 cleavage. In the AO-H2O2/UVC process, the electrogeneration of H2O2 can avoid the risks associated with the transportation, storage and manipulation of this oxidant and, furthermore, (OH)-O-center dot at the anode surface are also formed. Nevertheless, low contents of H2O2 were detected mainly at the beginning of the reaction, leading to a lower initial reaction rate when compared with the H2O2/UVC system. In the PEF-UVC, the addition of iron at neutral pH led to the visible formation of insoluble iron oxides that can filter the light. At pH 2.8, the iron remained dissolved, thereby promoting the Fenton's-reaction and increasing the organics removal. The UVA-driven processes showed limited efficiency when compared with those using UVC light. For all processes with H2O2 electrogeneration, the active chlorine species can be scavenged by the H2O2, diminishing the efficiency of the processes. This can explain the lower efficiency of AO-H2O2 when compared with AO. Moreover, the degradation of the MWWTP effluent spiked with 18 pharmaceuticals in mu g L-1 during AO process was assessed as well as the influence of the following operational variables on the process efficiency: (i) H2O2 concentration on H2O2/UVC, (ii) current density on AO, AO-H2O2, AO-H2O2/UVC, PEF-UVC and PEF-UVA, and (iii) pH on PEF-UVA.